The Work of Treason in the Age of User-Generated Content Revolution. Issue 1 (April 2015) - Anidjar, Gil
<x xml:space="preserve">Abstract</x> Gil Anidjar's essay reflects upon the occurrence of revolution in the context of user-generated content: as a self-promulgating and, purportedly, instantly consumable spectacle of power. Anidjar discusses the 'seeming collapse' of the temporal distance between the event and its narrative, its actor and its spectator, its survivor and its witness. Drawing on the valuation of spectatorship, in Immanuel Kant's insights on the French revolution, as embodying the significance of the event itself, and invoking the inherent element of 'danger' Kant perceived in the act of public utterance of judgment on the event, Anidjar suggests that such judgment may only, in Kantian terms, be responsibly pronounced in the immediate wake of the event as a manifestation of 'treason'. To seek to endow the revolutionary effort with the urgency of fame will be a necessarily premature gesture, and the shortening of the distance between the event and its judgment an impossible exercise, Anidjar argues, since 'we have not been granted the power to decide, much less to know whether, by our actions or reactions, we are betraying ourselves or our people or state, or whether we might be bringing about the faithful redemption of that which that people or that state of ours should already have been.'